2018
DOI: 10.1016/j.celrep.2017.12.102
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Restriction and Diet-Induced Weight Loss Do Not Induce Browning of Human Subcutaneous White Adipose Tissue in Women and Men with Obesity

Abstract: Caloric restriction (CR) is standard lifestyle therapy in obesity management. CR-induced weight loss improves the metabolic profile of individuals with obesity. In mice, occurrence of beige fat cells in white fat depots favors a metabolically healthy phenotype, and CR promotes browning of white adipose tissue (WAT). Here, human subcutaneous abdominal WAT samples were analyzed in 289 individuals with obesity following a two-phase dietary intervention consisting of an 8 week very low calorie diet and a 6-month w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 61 publications
5
45
1
1
Order By: Relevance
“…Our finding showing the induction of browning/beiging in SAT after SG-induced weight loss is in contrast to findings reported in adults after caloric restriction (84). A recent study in a large cohort of adults who were obese showed that caloric restriction and diet-induced weight loss diminishes browning features in SAT and that diet-induced changes in body fat are independent of subcutaneous abdominal WAT browning (84). The result and conclusion of the lack of activation of browning in the SAT depot induced by diet-induced weight loss cannot be extrapolated to bariatric surgery-induced weight loss.…”
Section: All Follow-up Patients (N = 9)contrasting
confidence: 99%
“…Our finding showing the induction of browning/beiging in SAT after SG-induced weight loss is in contrast to findings reported in adults after caloric restriction (84). A recent study in a large cohort of adults who were obese showed that caloric restriction and diet-induced weight loss diminishes browning features in SAT and that diet-induced changes in body fat are independent of subcutaneous abdominal WAT browning (84). The result and conclusion of the lack of activation of browning in the SAT depot induced by diet-induced weight loss cannot be extrapolated to bariatric surgery-induced weight loss.…”
Section: All Follow-up Patients (N = 9)contrasting
confidence: 99%
“…However, despite the changes observed in mRNA, the failure to find brown-like adipocytes and detectable levels of UCP1 protein within WAT of CR mice rather suggest that the browning of WAT in response to CR is negligible and irrelevant from a thermogenic point of view (39). Our data are further supported by a recent study in obese humans that also reported the absence of browning in response to CR (40). The lack of significant browning induced by CR contrasts with the tangible browning capacity of other agents, such as TZDs, which we showed were capable of inducing detectable levels of UCP1 in WAT (9,10).…”
Section: Discussionsupporting
confidence: 85%
“…A recent study in non-obese humans suggests that a two-year 25% CR regimen is feasible in non-obese humans; the only sex differences observed were a slightly lower BMI in the cohort that was predominantly women (69.7%) [6]. Notably, there are sex specific differences in brown and beige markers in adipose tissue of women, which are maintained after 8 weeks of CR [8]. It is encouraging to witness the inclusion of females in these very important clinical trials, but also to observe investigators reporting stratification of results by sex.…”
Section: Introductionmentioning
confidence: 99%